Sistema aquapônico integra produção de lambari-do-rabo-amarelo com alface lisa - AMARO, Luelyton Silva; WANDERLEY, Alysson Martins; MENDEZ, Victor Hugo Benassi; ACUNHA, Rubia Mara Gomes; CAMPOS, Cristiane Meldau (ANAIS DO ENIC, 2025)
-